2020
DOI: 10.17749/2070-4909.2019.12.4.279-290
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic analysis of using cyclin-dependent kinase 4 and 6 inhibitors in the first line treatment of HR-positive HER2-negative advanced breast cancer

Abstract: Фармакоэкономические аспекты применения ингибиторов циклинзависимых киназ 4 и 6 в первой линии терапии местнораспространенного или метастатического рака молочной железы Оптимизация лекарственного обеспечения пациентов со злокачественными новообразованиями на уровне субъекта Российской Федерации Оценка технологий здравоохранения в Австралии Том 12 2019 FARMAKOEKONOMIKA Modern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The results of the study were found to be in line with what emerged from the present work, as the comparison between the three CDK4/6i, PAL was found to be the most cost-effective. Furthermore, even in the study conducted by Avxentyev et al, 33 the use of PAL versus RIB in the Russian population was found to be the most cost-effective treatment option for postmenopausal HR+/HER2- patients with locally advanced MBC.…”
Section: Discussionmentioning
confidence: 84%
“…The results of the study were found to be in line with what emerged from the present work, as the comparison between the three CDK4/6i, PAL was found to be the most cost-effective. Furthermore, even in the study conducted by Avxentyev et al, 33 the use of PAL versus RIB in the Russian population was found to be the most cost-effective treatment option for postmenopausal HR+/HER2- patients with locally advanced MBC.…”
Section: Discussionmentioning
confidence: 84%
“…Table 2 summarizes the methodology of BIA studies. Six out of 17 studies included the budget impact model [26,28,30,[35][36][37], five Markov studies [29,33,38,41,42], two cohort-based studies [34,39], and other studies based on health-state modeling [27], health economic model (HEM) [32], and spread-sheet [31], and one study did not state it clearly [40]. All studies expressed their time horizon between 1 and 5 years, and four studies used lifetime [32,33,38,42].…”
Section: Methodology Of Included Studiesmentioning
confidence: 99%
“…Table 1 shows the general characteristics of the BIAs included in the study. Among them, about half (n = 8) of the studies were conducted in Europe [26][27][28][29][30][31][32][33], three in the United States [34][35][36], three in Asia [37][38][39], two in Russia [40,41], and one in Australia [42]. BIAs were performed in the period 2004-2021.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations